2013
DOI: 10.1073/pnas.1306389110
|View full text |Cite
|
Sign up to set email alerts
|

Essential ribosome assembly factor Fap7 regulates a hierarchy of RNA–protein interactions during small ribosomal subunit biogenesis

Abstract: Significance Ribosomes are complex macromolecular machines universal to all domains of life that synthesize all cellular proteins. They consist of many different protein and RNA building blocks. Their biogenesis—a paradigm for the assembly of macromolecular machines in general—is a highly complex and tightly regulated process in eukaryotes requiring the concerted action of many ribosome assembly factors. In this study we analyze the cross-talk between two of these assembly factors and ribosomal build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 32 publications
9
41
0
Order By: Relevance
“…For this, we monitored stimulation of ATPase activity of Fap7 and the Fap7-2 mutant protein using a coupled-enzyme assay that detects formation of ADP upon ATP hydrolysis (Montpetit et al, 2012). Consistent with previous studies (Hellmich et al, 2013; Loc'h et al, 2014), Fap7 alone shows no significant ATPase activity (Figure 4B). However, binding to uS11 stimulates its ATPase activity (Hellmich et al, 2013) as indicated by an increase in ADP formation over time.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For this, we monitored stimulation of ATPase activity of Fap7 and the Fap7-2 mutant protein using a coupled-enzyme assay that detects formation of ADP upon ATP hydrolysis (Montpetit et al, 2012). Consistent with previous studies (Hellmich et al, 2013; Loc'h et al, 2014), Fap7 alone shows no significant ATPase activity (Figure 4B). However, binding to uS11 stimulates its ATPase activity (Hellmich et al, 2013) as indicated by an increase in ADP formation over time.…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, uS11 forms a stable complex with the ATPase Fap7 (Granneman et al, 2005). Structural studies of the Fap7:uS11 complex revealed that Fap7 functions as a RNA mimic suggesting that it stabilizes uS11 before being incorporated into 40S ribosomes (Hellmich et al, 2013; Loc'h et al, 2014). Co-overexpression of FAP7 and uS11 together restored impaired growth of the P GAL1 - TSR2 mutant to nearly WT rates (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this, protein cross-linking identified Fap7 contacts with several proteins in the preribosomes [5]. An interaction between aFap7 and aNob1 has also been observed [19], but we have not been able to observe this interaction with the yeast homologues.…”
Section: Discussionsupporting
confidence: 78%
“…This interaction stimulates the ATPase activity of Fap7 (Hellmich et al, 2013), which is essential for its function in the translation-like cycle (Strunk et al, 2012). We have previously shown that the AF Dim1, a universally conserved methyltransferase, crosslinks to Fap7 in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…80S-like ribosomes accumulate in the absence of the essential ATPase Fap7 (Strunk et al, 2012), which also interacts with, and is activated by the small ribosomal protein Rps14 (Granneman et al, 2005; Hellmich et al, 2013; Loc’h et al, 2014). Furthermore, Fap7 was crosslinked to the AF Dim1 in vivo (Strunk et al, 2012).…”
Section: (Introduction)mentioning
confidence: 99%